PERKAMBANGAN PENDIDIKAN ISLAM DI PAKISTAN - Fitrina Martajasa (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
In the historical trajectory of Islamic civilization, the role of education can truly be actualized and applied, precisely in the era of Islamic glory, which was all a process of the long time that Muslims have been involved in the protection of Islamic sciences which originate from the Koran and As-Sunnah. We can see this, where education is truly able to shape civilization, so that Islamic civilization becomes the leading civilization as well as a civilization that colors the Arabian Peninsula, Africa, West Asia and Eastern Europe. For this reason, the existence of an educational paradigm that empowers students is a necessity. Islamic religious education in Pakistan is divided into 3 categories, namely: Quranic School, Mosque Primary School, and Madrasah. The education policy between Pakistan and Indonesia is almost the same, namely making education compulsory for their citizens. It's just that in Pakistan it is mandatory to study up to high school, while in Indonesia it is only up to junior high school.